The Influence of Profitability, Solvency, Firm Size on Stock Prices With Dividend Policy as Intervening Variable In Manufacturing Companies Listed on The IDX - Putri, Poppy Okta Fiana; Zefriyenni, Zefriyenni; Lusiana, Lusiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2024)
The aim of this research is to discover influence of profitability, solvency and firm size have on share prices with dividend policy as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2019-2023. There are 218 manufacturing companies listed on the Indonesian stock exchange in 2019-2023. Meanwhile, the sample for this research consisted of 54 companies which were included in manufacturing companies and were selected using purposive sampling. The analysis method used is linear multiple regression data analysis, using computer assistance with the SPSS 23 software program. Based on the research results, it shows that there is a significant influence (0.777 > 0.05) on policy profitability. There is no significant effect of solvency (0.396 > 0.05) on dividend policy. Firm size does not have a significant effect (0.079 > 0.05) on dividend policy. There is a significant influence of profitability (0.000 < 0.05) on share prices. There is no significant effect on solvency (0.998 > 0.05) on share prices. There is a significant effect of firm size (0.000 < 0.05) on share prices. There is a dividend policy that has no significant effect (0.708 > 0.05) on share prices. There is a dividend policy that does not mediate profitability on share prices. There is a dividend policy that does not mediate Solvency on Share Prices. There is a dividend policy that does not mediate firm size on share prices.